Simulating Trambouze reaction for a series reactor / Amizon Azizan and Nornizar Anuar - Azizan, Amizon; Anuar, Nornizar (Universiti Teknologi MARA, 2020)
Simulating the existing data on Trambouze reaction is compiled in this article. The objective of the work is to present the change of volumetric flow rate and the inlet concentration of key reactant A in a series continuous stirred tank reactor-plug flow reactor (CSTR-PFR) configurations. The volumetric flow rate does not affect selectivity and conversion for a constant volumetric flow rate operating condition, entering CSTR and PFR, at a specific concentration of reactant. The CSTR-PFR series reactor configuration is proposed for the aim of maximizing the selectivity of the desired product B in comparison to the undesired products X and Y. CSTR as the first reactor is capable to achieve the maximum conversion at the highest selectivity of A. PFR is then proposed after CSTR in a configuration of CSTR-PFR, to allow higher conversion value to be achieved for the resulted outlet stream conditions coming out of the first reactor, CSTR. Both reactors commonly encounter a decrease in the initial concentration of A and an increase to the formation of other products. The CSTR entering volumetric flow rate influence the volume sizes needed in achieving the maximum selectivity and conversion